Pengaruh Sharia competence, Creativity Dan Motivasi Terhadap Kinerja Karyawan Koperasi Tunas Artha Mandiri Syariah Kabupaten Jombang - Dwi Sri Devi Laila Mukaromah; Peni Haryanti (Journal of Economic and Islamic Research, 2024)
Competition in the Islamic finance industry, including Islamic cooperatives, nowadays the increasingly tight high level of competition in the Islamic finance industry can be influenced by the sharia competence, creativity, and motivation of employees, therefore the quality of Islamic Human Resources (HR) needs to be improved, especially in the context of national economic institutions. Especially sharia cooperatives. This study aims to determine the extent of the influence both partially and simultaneously on the sharia competence, creativity, and motivation factors on the performance of employees of the Tunas Artha Mandiri Syariah Jombang cooperative. This study uses an associative method with a quantitative approach. The population used as the object in this study is the employees of the Tunas Artha Mandiri Syariah Jombang cooperative. The sample determination method uses a non-probability sampling technique with a saturated method where the entire number of respondents is taken in its entirety, with a total sample of 50 people in TAM cooperative employee. Furthermore, the respondents' data was analyzed using data analysis techniques including validity tests, reliability tests, classical assumption tests, and hypothesis tests. The results of the study showed that partially and simultaneously sharia competence, creativity and motivation had a positive and significant effect on the performance of employees of the Tunas Artha Mandiri Syariah Jombang cooperative.